Proceedings Including the Charter of Good Practice in Using Public-Private Dialogue for Private Sector Development - World Bank (Washington, DC, 2013)
There has been growing interest from stakeholders around the world in recent years in how to build momentum for private sector development in states with poor investment climates. Dialogue between the public and private sectors, in various forms, has often been integral to attempts to build such momentum. It became increasingly clear that there was a demand from the field for guidance based on international best practice. In 2004-2005, responding to this demand, the World Bank, Department for International Development (DFID) and Organization for Economic Co-operation and Development (OECD) development centre independently conducted or commissioned reports drawing together lessons learned from field experiences in using public-private dialogue to promote private sector development reform efforts. While numerous case studies had existed, this was the first time comprehensive efforts had been made to synthesize lessons. The papers were: competitiveness partnerships, reforming the business enabling environment, and dialogue public-prive dans les pays en developpement. The development of the three papers in a short period indicated a growing recognition among the international donor community of the importance and potential of public-private dialogue as a tool for promoting private sector development with the ultimate aim of poverty reduction.